Persistent political engagement: social interactions and the dynamics of protest movements - Bursztyn, L; Cantoni, D; Yang, DY; Yuchtman, N; Zhang, YJ (American Economic Association, 2021)
We study the causes of sustained participation in political movements. To identify the persistent effect of protest participation, we randomly indirectly incentivize Hong Kong university students into participation in an antiauthoritarian protest. To identify the role of social networks, we randomize this treatment's intensity across major-cohort cells. We find that incentives to attend one protest within a political movement increase subsequent protest attendance but only when a sufficient fraction of an individual's social network is also incentivized to attend the initial protest. One-time mobilization shocks have dynamic consequences, with mobilization at the social network level important for sustained political engagement.